2015
DOI: 10.2320/matertrans.mh201404
|View full text |Cite
|
Sign up to set email alerts
|

Local Strain Fields of LPSO in Mg-Based Ternary Alloys

Abstract: L1 2 -type TM 6 RE 8 clusters are distributed in enriched layers of LPSO (long period stacking ordered structure), and shrink in the [0001] Mg direction. The growth mechanism of LPSOs was investigated from the viewpoint of a local strain field. The strength of out-of plane normal strain of the enriched layer varied with the average radius of solute elements in the layer. The first principle calculation showed that there is a relationship between the average atomic radius of solute elements and the structural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The average stacking fault density close to that of the 18R is realized because the number density of clusters, or the amount of solute atoms available for the microstructure formation is equivalent to the 18R long-range order, but once a stacking fault is introduced by chance, it is persistent and takes long time to change the position even if the distance between the neighboring stacking fault is less or more than 6 atomic planes. In much dilute alloys, formation of stacking faults/ and their extension in in-plane and out-of-plane directions have been examined by Kiguchi et al [21] and Kim et al [23] by TEM/HAADF-STEM. They discussed the transition mechanism from GP zones / clusters into LPSO structures, and argued that the introduction of stacking faults and motion of Shockley partial dislocations may drive growth of LPSO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average stacking fault density close to that of the 18R is realized because the number density of clusters, or the amount of solute atoms available for the microstructure formation is equivalent to the 18R long-range order, but once a stacking fault is introduced by chance, it is persistent and takes long time to change the position even if the distance between the neighboring stacking fault is less or more than 6 atomic planes. In much dilute alloys, formation of stacking faults/ and their extension in in-plane and out-of-plane directions have been examined by Kiguchi et al [21] and Kim et al [23] by TEM/HAADF-STEM. They discussed the transition mechanism from GP zones / clusters into LPSO structures, and argued that the introduction of stacking faults and motion of Shockley partial dislocations may drive growth of LPSO.…”
Section: Resultsmentioning
confidence: 99%
“…Since the driving force of the formation of LPSO structure contains a structural origin as shown by Iikubo et al [20], and a chemical origin as shown by Masumoto et al [26], these processes may proceed concomitantly or separately depending on the heat treatment conditions. In the solute lean samples such as Mg97Y2Zn1 or Mg98.5Y1Zn0.5, clusters, or GP zones in hcp lattice tend to form on a few basal segregation layers, which later transform into LPSO block structures after introduction of stacking faults [21]- [23], rather than uniformly dispersed in hcp matrix as observed in the concentrated alloys of Mg85Y9Zn6 alloys. The schematic illustration for the transition depicted in [17] suggests that it is natural to assume that the randomly distributed clusters transformed to LPSO structure via formation of such segregated, i.e., densely populated stacking fault layers.…”
Section: Kinetics Of Structural Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current century, it has found that a novel structure, so-called "synchronized long period stacking ordered structure (LPSO)" in Mg-TM-RE (TM: transition metals, RE: rare earth metals) alloy systems that show excellent mechanical properties in comparison with the conventional Mg alloys and Al alloys such as duralmin. 13) To date, the structure and the morphology of LPSO have been clarified in atomic scale in the early studies mainly by Z-contrast imaging using high-angle annular dark fieldscanning transmission electron microscopy (HAADF-STEM). 410) 9,10) Based on the diffuse scattering pattern in the electron diffraction patterns, they concluded that L1 2 -type clusters align in inplane short range order.…”
Section: Introductionmentioning
confidence: 99%